Efficiency of chelated fertilizers in sunflower cultivation - M. S. Sidakova (Новые технологии, 2024)
The article investigates the effect of innovative forms of fertilizers containing a full set of macro and microelements on the condition of plants, yield and quality of sunflower seeds in the foothills of the Kabardino-Balkarian Republic. ORGANOMIX brand M for oilseeds has a fungicidal effect and, having an immunity inducer and growth stimulator in its composition, promotes plant growth and the formation of seed tissues, an increase in overall yield, the accumulation of fat in seeds, and an improvement in the quality indicators of sunflower seeds. The article presents average data for the period 2021-2023. Sunflower has high requirements for the provision of soil with nutrients and is especially sensitive to boron deficiency. Double non-root treatment of sunflower plants in the phase of 2-3 and 4-6 pairs of true leaves with liquid chelated fertilizer ORGANOMIX oilseed, enhanced with the microelement BOR, has made it possible to obtain the highest yield under the experimental conditions - 26.4 c / ha of sunflower seeds. The quality of sunflower seeds plays a major role for agricultural producers. The fat content of seeds is the main quality characteristic and it depends on the husk content, which is determined by hereditary characteristics and the external environment has little effect on it. In our experiment, the highest oil content was obtained in the variant of using the ORGANOMIX oil fertilizer, enhanced with microelements BOR and ZINC in a mixture with ORGANOSTIM - 47.0%, the husk content varied from 24.5 to 25.9%.